Islamic Character Values in Hikayat Masyhud al-Hakk Volume II: A Philological and Cultural Analysis - Ach Hakiki; Dedi Supriadi; Jajang A. Rohmana; Usman Supendi (UIN Sunan Gunung Djati Bandung, 2026)
This article examines the values ​​of Islamic character in Hikayat Masyhud al-Hakk, volume II, through a philological approach and cultural analysis. This manuscript is not only a literary heritage but also a medium for character education, full of Islamic moral and spiritual values. This study aims to reveal forms of values ​​such as ḥikmah (wisdom), sidq (honesty), amanah (responsibility), shajāʿah (moral courage), tawakkul, and ikhlāṣ (sincerity), which are articulated in the actions and dialogues of the main characters, and enriched by the context of traditional Malay culture. The results of the study show that this tale combines Islamic values ​​with socio-customary norms through language symbolism, narrative structure, and local idioms. These findings emphasize the importance of classical tales as a source of character learning that is relevant to modern education based on local wisdom.